Mitogen-activated protein kinase pathway and four genes involved in the development of benign prostatic hyperplasia: in vivo and vitro validation - Gu, Jia-Min; Guo, Xing-Pei; Wu, Lan; Li, Lu-Yao; Zhu, Cong; Deng, Tong; Wang, Shuang-Ying; Fang, Cheng; Zeng, Xian-Tao (Frontiers in Immunology, 2025)
BackgroundBenign prostatic hyperplasia (BPH) is a common age-associated disorder characterized by non-malignant proliferation of prostate tissues. However, its underlying molecular mechanisms remain incompletely elucidated.MethodsA rat model of BPH was established via surgical castration followed by testosterone propionate administration. Proteomic profiling was performed on prostate tissues from BPH and sham-operated rats. Public datasets of BPH patients and healthy individuals were also analyzed to validate the translational relevance. In addition, qPCR was conducted on both rat tissues and human-derived prostate cell lines to confirm gene expression levels. Furthermore, immunohistochemistry was performed on prostate tissue samples from BPH patients to examine the expression and localization of the target proteins.ResultsProteomic analysis revealed significant upregulation of four proteins—QPCT, ARHGEF37, FLNC, and LGALS7—in BPH model rats compared with controls. KEGG pathway enrichment identified the MAPK signaling pathway as a potential key regulator of BPH progression. Similar expression patterns were observed in human datasets. qPCR results further validated the elevated expression of these four genes in both rat and human BPH-related samples. Immunohistochemistry further demonstrated that all four proteins were highly expressed in prostate tissues from BPH patients.ConclusionsThe aberrant overexpression of QPCT, ARHGEF37, FLNC, and LGALS7, along with dysregulation of the MAPK signaling pathway, may contribute to BPH pathogenesis. These findings provide new insights into the molecular mechanisms of BPH and may inform the development of diagnostic markers or therapeutic targets.